2020
DOI: 10.1111/jnc.15018
|View full text |Cite
|
Sign up to set email alerts
|

Water‐soluble variant of human Lynx1 positively modulates synaptic plasticity and ameliorates cognitive impairment associated with α7‐nAChR dysfunction

Abstract: Lynx1 is a GPI-tethered protein colocalized with nicotinic acetylcholine receptors (nAChRs) in the brain areas important for learning and memory. Previously, we demonstrated that at low micromolar concentrations the water-soluble Lynx1 variant lacking GPI-anchor (ws-Lynx1) acts on α7-nAChRs as a positive allosteric modulator. We hypothesized that ws-Lynx1 could be used for improvement of cognitive processes dependent on nAChRs. Here we showed that 2 µM ws-Lynx1 increased the acetylcholine-evoked current at α7-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 60 publications
1
64
0
Order By: Relevance
“…Interestingly, similar aggregation was previously observed for SLURP-2 [ 32 ], which also has a relatively high hydrophobicity index (+0.10, Table 1 ). The aggregation of Lynx2 and SLURP-2 was observed at concentrations > 0.1 mM, which are significantly higher than expected protein concentrations in the organism [ 15 ]; therefore, this aggregation, probably, has no biological consequences. One of the probable oligomerization interfaces in the Lynx2 molecule (Thr25-Val28) is located near the proposed glycosylation site (Asn23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, similar aggregation was previously observed for SLURP-2 [ 32 ], which also has a relatively high hydrophobicity index (+0.10, Table 1 ). The aggregation of Lynx2 and SLURP-2 was observed at concentrations > 0.1 mM, which are significantly higher than expected protein concentrations in the organism [ 15 ]; therefore, this aggregation, probably, has no biological consequences. One of the probable oligomerization interfaces in the Lynx2 molecule (Thr25-Val28) is located near the proposed glycosylation site (Asn23).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lynx1 is colocalized with α7- and α4β2-nAChRs in the brain [ 10 ] and modulates their function [ 11 ], in particular controlling an assembly of α4β2-nAChRs in the endoplasmic reticulum [ 12 ]. Lynx1 regulates neuronal plasticity during postnatal development [ 13 ], motor learning [ 14 ], and other cognitive functions by interaction with α7-nAChRs [ 15 ]. Similarly, Lynx2 (also known as LYPD1) is expressed in the peripheral and central nervous systems [ 16 ] and modulates α4β2-nAChRs [ 17 ], probably controlling their assembly [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a question about the permeability of the blood-brain barrier (BBB) for mambalgin-2 remains open. Recently, we showed that water-soluble domain of the nAChR modulator ws-Lynx1 crosses BBB in mice, despite the quite high molar mass of the protein (~8 kDa) [57]. We proposed that ws-Lynx1 can penetrate BBB by transcytosis via interaction with nAChRs expressed on endothelial cells [57].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that water-soluble domain of the nAChR modulator ws-Lynx1 crosses BBB in mice, despite the quite high molar mass of the protein (~8 kDa) [57]. We proposed that ws-Lynx1 can penetrate BBB by transcytosis via interaction with nAChRs expressed on endothelial cells [57]. Besides nAChRs, human brain endothelial cells express ASIC1a [58], so we suppose that mambalgin-2 can also pass through BBB by transcytosis, however further investigation of this issue is required.…”
Section: Discussionmentioning
confidence: 99%
“…Lynx1 has been shown to regulate plasticity in the hippocampus (20,21), alter plasticity in the adult visual and auditory cortices (20) and suppress associative learning and memory (9). More specifically, it has been shown to associate with α4β2-nAChRs and to increase the rate of receptor desensitization to acetylcholine (22).…”
Section: Accepted Articlementioning
confidence: 99%